2022
DOI: 10.3390/pharmaceutics14020354
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogene Variants Associated with Liver Transplant in a Twelve-Year Clinical Follow-Up

Abstract: Some gene polymorphisms have been previously associated individually with tacrolimus efficacy and toxicity, but no long-term study to determine the role of pharmacogene variants in the clinical evolution of liver-transplanted patients has been addressed so far. In the present work, we analyzed the relation between highly-evidenced genetic polymorphisms located in relevant pharmacogenes and the risk of suffering premature death and other comorbidities such as cancer, diabetes mellitus, arterial hypertension, gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Twelve-year clinical research on pharmacogene variants associated with liver transplantation showed that variants in different locations of the ABCC2 transporter genes were associated with a lower risk of T2DM. [ 48 ] A review of 485 participants, including 10 cross-sectional studies, revealed significant changes in liver transporters during the progression of NAFLD to NASH compared with the control group. NAFLD progression is associated with reduced expression and function of several hepatic uptake transporters, upregulation of many efflux transporters, downregulation of cholesterol efflux transporters, and mislocalization of the canalicular transporter ABCC2.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve-year clinical research on pharmacogene variants associated with liver transplantation showed that variants in different locations of the ABCC2 transporter genes were associated with a lower risk of T2DM. [ 48 ] A review of 485 participants, including 10 cross-sectional studies, revealed significant changes in liver transporters during the progression of NAFLD to NASH compared with the control group. NAFLD progression is associated with reduced expression and function of several hepatic uptake transporters, upregulation of many efflux transporters, downregulation of cholesterol efflux transporters, and mislocalization of the canalicular transporter ABCC2.…”
Section: Discussionmentioning
confidence: 99%
“…Several genetic variants have been described to influence TAC therapy, highlighting those involved in its metabolism and transport. The most relevant variant affecting TAC metabolism is c.6986A > G of the CYP3A5 gene, which results in a premature stop, generating a non-functional enzyme [ 7 , 8 ]. However, this variant is highly variable between ethnicities, being predominantly present in 94% of the European population, but in just 18% of Africans and 67% of South Asians [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Foods can affect the bioavailability of this drug, especially those rich in fat. TAC AEs are documented in the literature as very being frequent, including hyperglycemia, muscle pain, nephrotoxicity and gastrointestinal effects (diarrhea) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Continuing in the line of transplantation, several original research papers and reviews on the pharmacogenetics of tacrolimus were accepted in this Special Issue. As more novel associations, MTHFR rs1801133 in the donor and MTHFR rs1801131 in the recipient were related to survival rate variations in a 12-year follow-up period [ 9 ]. This gene is considered a very important pharmacogene (VIP) related to methotrexate toxicity.…”
mentioning
confidence: 99%